PENGARUH PENDIDIKAN MORAL DAN KOMPETENSI SOSIAL GURU TERHADAP PEMBENTUKAN KARAKTER SISWA SMP MANBA’UL ULUM JAKARTA - Syamsul Bahri Tenrere; Farizal Farizal; Ahmad Rifa'i (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2020)
This research is a quantitative research, data collection was done by collecting primary and secondary data sources. The sample of this study was 89 respondents using random sampling from a total of 382 students of SMP Manba'ul Ulum, West Jakarta. The coefficient of reliability test results for moral education is 0.907, the results of the reliability test for the Social Competence of Teachers are 0.912, and the results of the reliability test for character building are 0.915. Hypothesis using inferential test. The results showed that improving moral education at SMP Manba'ul Ulum was carried out by: routine activities, spontaneous activities, exemplary, conditioning, integration of moral values in every subject, culture as if, and involving all components in school to improve character building students by way of introduction, understanding, exemplary and habituation. In order for the social competence of teachers to be better, it must be improved by training, seminars, reading literacy books regarding teacher competence and further studies.